2013
DOI: 10.15845/njsr.v4i0.264
|View full text |Cite
|
Sign up to set email alerts
|

Placed in homecare: Living an everyday life restricted by dependence and monitoring

Abstract: Through a sociological case study this article analyses how, seen from a relational perspective, everyday life for elderly people receiving care in their own homes is lived with dependence on health-care professionals. The healthcare professionals' time and tasks are assigned and allocated in advance so that the elderly people are neither allowed nor able to vary their response in relation to the situation they encounter. The life of the client is also treated as though it were a solid, structured everyday lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…The theoretical concepts of power, disciplining and normalisation have through many years provided an alternative view for research about the medical clinic, professionals and patients (Campbell, 2011;Cook & Brunton, 2015;Glasdam, Praestegaard, & Henriksen, 2013;Jones, 2018;McCabe & Holmes, 2014;McCarthy, 2010;Rose, 1990Rose, , 1994). Foucault regarded power as a relation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The theoretical concepts of power, disciplining and normalisation have through many years provided an alternative view for research about the medical clinic, professionals and patients (Campbell, 2011;Cook & Brunton, 2015;Glasdam, Praestegaard, & Henriksen, 2013;Jones, 2018;McCabe & Holmes, 2014;McCarthy, 2010;Rose, 1990Rose, , 1994). Foucault regarded power as a relation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This means that although professional and political intentions are to equalize power relationships, the concrete actions which result from meetings between healthcare professionals and patients have an inherently imbalanced power structure which is reinforced by these meetings. By extension, Holen & Arhenkiel (2011) and Glasdam et al (2013aGlasdam et al ( , 2013b show how neoliberal discourses have the effect of narrowing the space for patient involvement in clinical practice. Apparently, the physicians and the nurses share their knowledge as best as they can and try to appear confident and persuasive when giving the information, but the information is difficult to understand for the patients within a tight consultation schedule.…”
Section: Two Different Interests In Disease and Treatment Are At Playmentioning
confidence: 99%
“…Denmark is increasingly being influenced by marketization principles organizing healthcare (Bertelsen & Rostgaard, ). The entire society and thus also the healthcare system are organized as services based on neoliberal bureaucratic regulations and ideas (Mik‐Meyer & Villadsen, ; Holen, ; Glasdam et al ., , ), that is, political ideas based on minimizing public costs, privatizing as many welfare services as possible, and emphasizing individual freedom, especially in acting and expressing oneself freely (Harvey, ). A study of white papers (public health policies) in Scandinavian countries has shown that Denmark is more neoliberal than the other Scandinavian countries, stressing the importance of individual behaviour, responsibility, and autonomy when it comes to public health policies (Vallgårda, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature on care, it is common to highlight time and discretion as key components in care work because it takes time to build a trusting relationship and to organise the work around the needs of the recipients of care (Abel & Nelson, 1990). There has long been an agreement in the research that paid care work in bureaucratically organised institutions leads to tension for caregivers since the organisation, rigid scheduling and managerial control of work contradicts the flexibility and affective involvement required to give individually tailored care (Abel & Nelson, 1990;Glasdam, Praestegaard, & Henriksen, 2013;Waerness, 2004). Waerness (2004), one of the staunchest critics of the socio-political planning of public care, claims that the modernisation processes of recent years run counter to what is distinctive about the rationality of care work.…”
Section: Care In Health Service Institutionsmentioning
confidence: 99%